Oltar sv. Jurja Antonija Michelazzija iz stare Zagrebačke katedrale - kontekst narudžbe - Šourek, Danko (2007)
Godine 1741. riječki kipar Antonio Michelazzi sklopio je sa zagrebačkim kanonicima Jurjem Rešom (Georgius Reess/Rees) i Jurjem Dumbovićem (Georgius Dumbovich) ugovor o izradi Oltara sv. Jurja za Zagrebačku katedralu, obvezavši se da će posao dovršiti do 1743. godine. Izvršenje narudžbe produljilo se, međutim, sve do 1746. godine. Budući da su oba prvotna naručitelja oltara umrla ne dočekavši njegovo postavljenje, brigu oko dovršetka naručenoga djela preuzimaju dvojica novih naručitelja – kanonici Juraj Reš mlađi (Georgius Reess/Rees) i Stjepan Puc (Stephanus Pucz/Putz). Iako nastavljaju suradnju s istim kiparom, dolazi do određenih promjena, prvenstveno u ikonografskom programu djela, očitovanih redefiniranjem atičke zone i postavljanjem statue bl. Augustina Kažotiča (1749.). U naručiteljskom je smislu kao nositelja tih promjena moguće izdvojiti zagrebačkoga kanonika i kasnijega velikoga prepozita Stjepana Puca kao naručitelja izgrađena umjetničkoga ukusa, ali i osobu aktivno uključenu u promicanje kulta bl. Augustina Kažotića, koji sredinom 18. stoljeća doživljava svojevrstan procvat u okviru Zagrebačke biskupije.
On 14. October 1741, Zagreb canons Juraj Reš (Georgius Reess/Rees) and Juraj Dumbović (Georgius Dumbovich) signed a contract with Antonio Michelazzi, a sculptor from Rijeka, in wich they commissioned him to design the altar of St George. Michelazzi guaranteed that he would produce the altar by April 1743 at the latest and place it in the chapel of the same name, which the afore-mentioned canons inteneded to build along the northern wall of Zagreb cathedral. However, an annex to the contract from 16 August 1746 shows that the altar was transported to Zagreb and placed into the cathedral only that year. Since the chapel had never been built, the altar was placed into the northern nave of the cathedral. In the meantime, the canons died (Dumbović in 1743 and Reš in 1745) and the supervision of the commission was taken over by canons Stjepan Puc (Stephanus Pucz/Putz) and Juraj Reš the Younger (Georgius Reess/Rees) – nephew of the late canon Juraj Reš the Elder. As soon as the altar was placed into the cathedral (1746), the new commissioners signed a deal with Michelazzi, ordering a statue of Bl. Augustin Kažotić ant two putti, which were placed onto the attic ending of St George's altar, apparently not earlier than 1749. This intervention into the original iconographic programme of the altar, motivated by the relatively common wish of the first commissioners to be buried before the altar of their patron saint (St George) is highly interesting, since the programme was already abandoned when the construction of St George's chapel was cancelled and the two canons were buried in diferent places within the cathedral. One may presume that the central role in choosing Bl. Augustin Kažotić – a 14th-century bishop of Zagreb – and making him a co-titular saint of the altar by placing his statue in the centre of the attic ending was played by Stjepan Puc, who had inherited the position of cathedral guardian from canon Juraj Reš the Elder, thus taking over, together with the late canon's nephew, the care for completing the initiated commission. Stjepan Puc would become an important provost and bishop of Belgrad and Smederevo, while by the time we are concerned with he had already been actively involved in promoting the cult of Bl. Augustin Kažotić, which relates him to various artworks with the theme of that saint within the cathedral of Zagreb. The prominence of Bl. Augustin Kažotić in the diocese of Zagreb around the middle and in the second half of the 18th century can be plausibly connected to his contribution to a specifically Zagreb liturgical order: the Ordo Goricensis. That particularity, maintained in the cathedral, managed to survive the Tridentine regulations regarding the uniformity of divine service throughout the Catholic Church, but was abolished in 1788. and 1794, owing to an intensified centralizing pressure from the Viennese court. Apparently, the intense veneration of Augustin Kažotić as a liturgical reformer can be explained as a sort of reaction to the social processes in the mid-18th century, in which the church of Zagreb sought to retain its identity and its significance by accentuating its specific tradition.
Projekt MZOS
HRV